Civil Law Forms of Protection Relations - D. N. Karkhalev (Сибирское юридическое обозрение, 2023)
The actual problems of the protection of civil rights and responsibility in the implementation of the protective function of civil law are considered. Forms of protective relations are proposed to be divided into four types: penal, restorative, preventive and provisional. The penal form is different in that it implements liability measures. Adverse property impact on the offender is a qualifying sign of responsibility and in most cases allows one to distinguish between liability measures from other coercive measures available in the arsenal of civil law. It is characterized by the imposition on the offender of certain property deprivations, encumbrances. The restorative form is characterized by the application of protective measures. Civil law protection measures are characterized by the fact that in terms of content they are not non-equivalent property deprivation and are applied forcibly or are carried out voluntarily in the form of restoring the situation that existed before the violation, or suppressing actions that violate the right (or threaten to violate it), or recognize subjective right (or fact). The preventive form is aimed at the implementation of self-defense measures. The main feature of self-defense measures is their compensatory nature. It is expressed in the fact that self-defence measures are applied in case of violation of a subjective civil right (or in case of a threat of its violation) in order to protect the violated right. In connection with these features, self-defense is classified as a means of protecting civil law. Provisional form - measures of an operational nature, are applied extrajudicially unilaterally, regardless of the consent of the offender to their implementation (that is, they are coercive measures). Operational measures are characterized by a security feature, which is expressed in stimulating the participants in civil circulation to the proper fulfillment of obligations.